Thermal analysis of formation of nano-crystalline BaTiO3 using Ba(NO3)2 and TiO2 - Ansaree M.J.; Upadhyay S. (My University, 2025)
The reaction of Ba(NO3)2 with TiO2 was studied by thermogravimetric (TG) and differential scanning calorimetric (DSC) techniques up to 1000 °C and in nitrogen atmosphere. It was found that the formation of BaTiO3 takes place above 600 °C and that precursor mixing time and heating rate have no effect on the reaction temperature. BaTiO3 powder was prepared by calcination of Ba(NO3)2 and TiO2 precursor mixture at 800 °C for 8 h. X-ray diffraction analysis of the synthesized BaTiO3 confirmed the formation of tetragonal phase with lattice parameters a = 3.9950±0.0003Å and c = 4.0318±0.0004Å. Thermal analysis of the synthesized BaTiO3 powder showed weight loss within temperature range 40-1000 °C of only 0.40%. This small amount of weight loss was connected with some impurity phase, and identified as BaCO3 using Fourier transforminfrared (FTIR) technique.